EXPERT SYSTEM DEVELOPMENT TO IDENTIFY EMPLOYEE PERSONALITY TYPES USING DEMPSTER SHAFER THEORY - Julia Fajaryanti; Rogayah Rogayah (Jurnal Riset Informatika, 2022)
Human resources are an essential asset for the company to develop and realize the company's goals. One of the efforts to optimize the capacity of employees is to know their personality. Personality is the form an individual possesses in behaving and all the characteristics that distinguish one individual from another. Understanding employees' personality is essential for the company and the employees themselves. Because by knowing a person's personality, the company can maximize the potential of employees and place certain positions that suit the employee's personality. This study aims to implement the dempster-Shafer theory on an inference engine in building an expert system to identify employee personality types. Dempster-Shafer's approach can perform probability calculations so that evidence can be carried out based on confidence and logical reasoning. The system developed can identify the employee's personality type through the nature or symptoms that exist in the employee. In addition, the system can display the diagnosis results with an explanation of the personality type, its character in work and occupations or positions suitable for that personality type. Based on the results of the accuracy-test obtained from the comparison of expert system diagnoses with the analysis of an expert, the accuracy value reaches 85%.